(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Ambulance paramedics’ work is often physically and emotionally taxing, and it may put a lot of strain on the person doing the profession. Their social and personal lives, as well as their health, might be impacted by their jobs. Studying paramedics’ psychological and social coping techniques in light of their long-term health and wellbeing was the major goal of the investigation in this study. It was also a secondary goal to look at how paramedics currently use peer support programmes and other referral services. Interviews with ambulance paramedics were used to gain a deeper understanding of their daily experiences. An individual’s storey can be documented in their own words via qualitative research. Within Rural Ambulance Victoria, there were nine rookie paramedics (firstyear) and 12 long-term paramedics (five or more years of service). Additionally, participants were chosen to represent a cross-section of the paramedic workforce in terms of gender.It’s clear that paramedics’ families and social lives have been adversely affected by the trauma they’ve witnessed, and they use a variety of coping strategies—both functional and dysfunctional—to deal with it. Moreover, there is evidence that many paramedics have, or are, suffering from acute and chronic PTSD.These findings will aid our knowledge of paramedics’ daily routines. An educated examination of what paramedics themselves regard to be important and accessible within the organisational support framework can help shape "best practises" in enhancing paramedics’ health.